Power system voltage stability analysis and control with facts - Luu, Ba Dien; Ho , Van Hien (Journal of Technical Education Science, 2010)
FACTS devices are used for controlling transmission voltage, power flow, reducing reactive losses, and damping of power system oscillations for high power transfer levels. One of the major causes of voltage instability in power system is the reactive power limit of the system. Power reactive control of power network with FACTS is a remedy for prevention of voltage instability and capable of increasing the power transfer capability of a line, insofar as thermal limits permit. In this paper, the programe language MATLAB is used for modelling and simulation for voltage control of the power system with FACTS.